Test Data Generation for Event Driven System Using Bees Algorithm - Mohammed Zabil, Mohd H.; Kamal Z., Zamli (2013)

(untitled)
For an event driven system, the order of the event sequence should also be tested to detect failure in any possible sequences of the event. In many real time or reactive system, some faults do occur as a result interactions of some particular order of the inputs or events. In some other systems, sequence of inputs produce significant results to how such system process the inputs and produce the output. For these types of systems, fault might be triggered from a particular order of the input sequence, entered or given to the system. . In this paper we discuss and proposed a new strategy for generating test data for event-driven system using a bio inspired artificial intelligent, namely Bees Algorithm (BA). We discussed the implementation of BA and benchmark it with the existing approaches.